Supervisi Akademik Kepala Sekolah dalam Upaya Meningkatkan Profesionalisme Guru di SMP Negeri 26 Palembang - Ervinna Hasdawaty; Syarwani Ahmad; Mahasir Mahasir (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to identify and describe the aspects that are supervised by the head master in an effort to help improve teacher professionalism, approaches to academic supervision, academic supervision techniques, describe the steps of academic supervision, describe the problem faced in supervision. Academics by the principal in an effort to help efforts to help improve teacher professionali at SMPN 26 Palembang in teaching. This study use a qualitative method. Data colletion techniques are interviews, observation and documentation. Date wew analyzed using interview analysis techniques, observation and documentation. The results show that it shows that teacher are already good at teaching but must be even more active in using ICT in information and communication technology in learning to improve their professionalism an professional teacher. Either with professional improvement training or training held by the Ministry of education or the head of SMPN 26 Palembang. Because a teacher who is said to be a professional is a teacher who meets standar requirements both in term of academics, competence, profession, and performance as a teacher.